Legume Plants Enhance the Resistance of Soil to Ecosystem Disturbance - Gao, Dandan; Wang, Xiaoling; Fu, Shenglei; Zhao, Jie (Frontiers in Plant Science, 2017)
Cultivation of legume plants is well known to improve soil N level and net primary productivity; besides, it may deliver other ecosystem benefits such as increasing soil carbon sequestration and soil food web complexity. However, little is known about whether legumes can improve the resistance of soils to ecosystem disturbances. In the present study, we compared the resistance of soils to an ecosystem disturbance (understory removal) in the presence or absence of a legume species (Cassia alata) in mixed tree species plantations in southern China. Soil physico-chemical and biotic properties were employed to quantify the resistance of soils to understory removal. Our results showed that the resistance indices of soil water content, omnivorous-predacious nematode abundance and nematode channel index to understory removal were greater in the presence of legumes than those without legumes in wet season. The resistance indices of fungal to bacterial ratio, fungivorous nematode abundance and total arthropod abundance were greater in the presence of legume than those without legume species in dry season. Our results indicate that legumes may enhance the resistances of soil physico-chemical and biological properties to the ecosystem disturbance. Our findings could provide a better understanding of the myriad ways in which legumes can positively affect ecosystem functioning.